2017
DOI: 10.1021/acs.molpharmaceut.6b01066
|View full text |Cite|
|
Sign up to set email alerts
|

Potential Eye Drop Based on a Calix[4]arene Nanoassembly for Curcumin Delivery: Enhanced Drug Solubility, Stability, and Anti-Inflammatory Effect

Abstract: Curcumin is an Indian spice with a wide spectrum of biological and pharmacological activities but poor aqueous solubility, rapid degradation, and low bioavailability that affect medical benefits. To overcome these limits in ophthalmic application, curcumin was entrapped in a polycationic calix[4]arene-based nanoaggregate by a simple and reproducible method. The calix[4]arene-curcumin supramolecular assembly (Calix-Cur) appeared as a clear colloidal solution consisting in micellar nanoaggregates with size, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 51 publications
2
60
0
1
Order By: Relevance
“…Finally, the biosynthesized Pd NPs are purified and washed via centrifugation [ 51 ]. It is worth mentioning that few recent studies reported on the use of supramolecules (macromolecules) such as calix[n]arenes and cyclodextrins as potential stabilizing agents for the biosynthesized Pd NPs [ 52 , 53 , 54 , 55 , 56 ]. They have been chosen as promising capping agents due to their biocompatible and eco-friendly nature [ 57 ].…”
Section: Mechanism Of Biogenic Synthesis Of Pd Npsmentioning
confidence: 99%
“…Finally, the biosynthesized Pd NPs are purified and washed via centrifugation [ 51 ]. It is worth mentioning that few recent studies reported on the use of supramolecules (macromolecules) such as calix[n]arenes and cyclodextrins as potential stabilizing agents for the biosynthesized Pd NPs [ 52 , 53 , 54 , 55 , 56 ]. They have been chosen as promising capping agents due to their biocompatible and eco-friendly nature [ 57 ].…”
Section: Mechanism Of Biogenic Synthesis Of Pd Npsmentioning
confidence: 99%
“…It was shown that transition from linear to star-shaped macromolecules significantly increases the polymer's ability of molecular recognition [3,4]. Special attention is paid to the derivatives of polyethylene oxide and polyalkyloxazolines, which is resulting from their biocompatibility and the ability to show low critical solution temperature (LCST) behavior, which allows controlling the processes of complexation of low-molecular compounds [5][6][7][8]. It should be pointed out that incorporation into the polymer of such moieties as macrocycles, for example calixarenes, cyclodextrins, etc., leads to a significant increase of the affinity of these macromolecules to low-molecular compounds and metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…A rat model of anterior uveitis, induced by LPS was also evaluated with the same results, the application of curcumin/calix [4]arene decreased ocular inflammation and reduced inflammation proteins to a higher extent than free curcumin. It also reduced ICAM-1 by the suppression of NF-κB [95].…”
Section: Encapsulationmentioning
confidence: 92%